2017
DOI: 10.1186/s12885-017-3090-2
|View full text |Cite
|
Sign up to set email alerts
|

Stromal alterations in ovarian cancers via wavelength dependent Second Harmonic Generation microscopy and optical scattering

Abstract: BackgroundOvarian cancer remains the most deadly gynecological cancer with a poor aggregate survival rate; however, the specific rates are highly dependent on the stage of the disease upon diagnosis. Current screening and imaging tools are insufficient to detect early lesions and are not capable of differentiating the subtypes of ovarian cancer that may benefit from specific treatments.MethodAs an alternative to current screening and imaging tools, we utilized wavelength dependent collagen-specific Second Harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…The SHG effect is an emerging field of biomedical microscopy, bioimaging and diagnostics for a wide range of diseases . For example, SHG microscopy was applied as a cancer diagnostic tool to probe the structural differences in the extracellular matrix of normal stroma, benign tumors, endometrioid tumors, and more . Furthermore, SHG microscopy was used to identifying articular osteochondrosis in pigs, and as an early diagnostic tool for corneal related diseases and imaging of collagen distributions in human sclera .…”
Section: Bioinspired Peptide Nanostructures: Basic Linear and Nonlinementioning
confidence: 99%
See 1 more Smart Citation
“…The SHG effect is an emerging field of biomedical microscopy, bioimaging and diagnostics for a wide range of diseases . For example, SHG microscopy was applied as a cancer diagnostic tool to probe the structural differences in the extracellular matrix of normal stroma, benign tumors, endometrioid tumors, and more . Furthermore, SHG microscopy was used to identifying articular osteochondrosis in pigs, and as an early diagnostic tool for corneal related diseases and imaging of collagen distributions in human sclera .…”
Section: Bioinspired Peptide Nanostructures: Basic Linear and Nonlinementioning
confidence: 99%
“…c) SHG images of representative and ovarian tumors obtained at 890 nm excitation, and its histology image. Reproduced under the terms of the CC‐BY 4.0 license ( https://creativecommons.org/licenses/by/4.0/) . Copyright 2017, the Authors, Published by BioMed Central Ltd. d) Collagen distributions in SHG images of a piece of human sclera.…”
Section: Bioinspired Peptide Nanostructures: Basic Linear and Nonlinementioning
confidence: 99%
“…Knowledge of the TACS-3 has the potential to improve diagnostic capabilities (Conklin et al, 2011). Another recent application includes work using ECM properties as determined by SHG imaging as a biomarker to delineate different subtypes of ovarian cancer (Tilbury et al, 2017). …”
Section: Advanced Imaging For Visualization Of Collagen and Other Ecmmentioning
confidence: 99%
“…This is a significant limitation as the native ECM in most tissues has intrinsic 3D architecture, where not all the collagen fibers lie in the plane of incidence or at small tilt angles relative to the plane. For example, the dermis and ovarian stroma in normal tissues have 3D mesh-like morphologies [9,10], and SHG will not visualize the entire structure. We previously have shown that 3D texture analysis provides significantly improved discrimination between ovarian tumors over the analogous 2D approach even using the incomplete information in 3D stacks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, this affords detection only of backward SHG emission, where retroreflected photons are collected by the excitation objective. This limits the SHG signal that can be collected, as the majority of photons are emitted in the forward direction, as well as precludes the use of directional-based metrics, which can be used for structural analysis [9,10]. …”
Section: Introductionmentioning
confidence: 99%